Evaluation of humoral immune response conferred by purified chick embryo cell vaccine (PCECV) and purified vero cell vaccine (PVCV) used in complete and mixed preexposure schemes at Pasteur Institute of São Paulo - Cunha Neto, R. S.; Cunha, R. S.; Chaves, L. B.; Scheffer, K. C.; Caporale, G. M. M.; Silva, A. C. R. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The most widely used vaccines in the Western world for human rabies prophylaxis are Purified Chick Embryo Cell Vaccine (PCECV) and Purified Vero Cell Vaccine (PVCV), which is used at Pasteur Institute of São Paulo since 2000. Whereas in Brazil there are no reports of the use of PCECV in replacement or complementation to PVCV, the aim of this study was to evaluate humoral immune response of people vaccinated against rabies in complete and mixed pre-exposure schemes using PCECV and PVCV with different routes of application, intramuscular (IM) and intradermal (ID). According to the vaccination scheme received, 115 serum samples from different individuals were distributed in seven groups: three containing serum samples from patients who received complete schemes with one vaccine and one route of application – 3 PVCV (IM), 3 PVCV (ID) e 3 PCECV (IM) -, used as reference; and four containing serum samples from patients who received both vaccines and two routes of application, featuring a mixed scheme – 2 PVCV (ID) + 1 PCECV (IM), 1 PVCV (ID) + 2 PCECV (IM), 2 PCECV (IM) + 1 PVCV (ID) e 1 PCECV (IM) + 2 PVCV (ID). The humoral immune response was analyzed based on the levels of rabies virus neutralizing antibodies (RVNA) obtained by rapid fluorescent focus inhibition test (RFFIT); through calculation of its maximum and minimum values, median, standard deviation, 1st and 3rd quartiles, interquartile range and Kruskal-Wallis test. Differences statistically significant (p-value < 0.05) were observed when the group 2 PVCV (ID) + 1 PCECV (IM) was compared with the groups 3 PVCV (IM) and 1 PCECV (IM) + 2 PVCV (ID). The group containing serum samples from patients who received 2 PVCV (ID) + 1 PCECV (IM) is the one responsible for statistical differences observed, because it is the group in which higher RVNA titers were detected, ie, the group with the best humoral immune response. Despite the differences observed, in all serum samples, RVNA titers obtained can be considered adequate (≥0.5 UI/mL), regardless of the vaccine and routes of application used. The use of PCECV for rabies vaccination, in complete or mixed pre-exposure scheme, showed satisfactory results in the induction of humoral immune response and its use may be adopted when it is necessary to complement or replace PVCV. Financial Support: Instituto Pasteur, São Paulo/SP, Brasil.